Analisis Pondasi Tiang Pancang Berdasarkan Hasil Perhitungan dan Loadding Test - Nusa Setiani Triastuti; Indriasari Indriasari (Universitas Trisakti, 2019)
Pile foundation is one of the solutions of high-rise buildings not in the area of restrict area. When the pile foundation reached until the hard ground reaches, a small settlement is expected and different setlement are not occur. The objective: analyze the results of loading tests compared carryng capacity calculations, pile cap thick required secure.The research method used in this research is the case study of pile foundation twelve floors building in Batam island. The reaction on the pile is analyzed using software program of non-linear structure version 9.5 which is supported by primary data, namely loading test and secondary data of soil investigation and the largest column force taken on the pole 1.618,854 ton, Mx -7,936 ton meter, My -75,531 ton meter.Carrying capacity analysis is based on friction and end bearing and calculated pole efficiency. The axial load of the plan is supported by 16 (sixteen) piles, based on the loading test (P) the ultimate pile foundation reaches 200% (two hundred percent) in the amount of 411.52 tons. Single pile carrying capacity is 205.76 tons .Settlement in the loading test results 10mm is smaller than from the setlement in calculation results. The stress acting on the pile cap of 12.453 kg/cm2 is smaller than the permit strees of 13 kg/cm2.